The Film Theory Reader. Debates and Arguments - Flores Villela, Carlos Arturo (Imagofagia, 2021)
Sobre Furstenau, Marc, (Coord.), The Film Theory Reader. Debates and Arguments. New York, Routledge, 2010, 304 pp. ISBN 10-0415-49322-6 Palabras clave: reseña, Marc Furstenau, The Film Theory Reader. Debates and Arguments